1998
DOI: 10.1111/j.1540-8159.1998.tb01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Infections with Nonthoracotomy Implantable Cardioverter Defibrillators: Can These Be Prevented?

Abstract: Nonthoracotomy ICDs are believed to be the best therapeutic modality for treatment of life-threatening ventricular arrhythmias. Little is known about the risk of infection with initial implantation of these devices. We studied the incidence, clinical characteristics, and risk factors associated with infections in 1,831 patients with nonthoracotomy ICD from the Endotak-C nonthoracotomy lead registry of Cardiac Pacemakers, Inc. A transvenous lead was implanted in 950 patients (51.9%) and a combination transvenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 67 publications
0
31
0
2
Order By: Relevance
“…Previous studies have shown that CDI occurs in 0.13% to 19.9% of permanent pacemakers 2,3,5,8,11 and 0.8% to 1.3% of transvenous non-thoracotomy implantable cardioverter-defibrillators. 7,17,26 The most relevant clinical question, however, is not the overall incidence of CDI among patients with these devices but rather the incidence of CDI in patients who present with SAB. The present study answers this question with several key observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that CDI occurs in 0.13% to 19.9% of permanent pacemakers 2,3,5,8,11 and 0.8% to 1.3% of transvenous non-thoracotomy implantable cardioverter-defibrillators. 7,17,26 The most relevant clinical question, however, is not the overall incidence of CDI among patients with these devices but rather the incidence of CDI in patients who present with SAB. The present study answers this question with several key observations.…”
Section: Discussionmentioning
confidence: 99%
“…Although Staphylococcus aureus is an important cause of CDI, 4,7,10,[12][13][14][15][16][17][18] the risk of developing CDI after S aureus bacteremia (SAB) is inadequately defined. This uncertainty complicates patient management.…”
mentioning
confidence: 99%
“…ICD pocket infections are rare. The overall incidence of infections ranged from 0.5-2.2% of patients in a review [10]. Several risk factors for ICD infection have been reports among them, male sex, lack of antimicrobial prophylaxis during the implantation procedure, the number of prior cardiac implantation procedures, and type of device [11].…”
Section: Discussionmentioning
confidence: 99%
“…6 Various observational studies suggest that device infection rates range from 1% to 7%. [7][8][9][10][11] In general, implantable cardioverter-defibrillators have a higher rate of infection compared with pacemakers. 12 Factors that increase the risk of device infection include diabetes mellitus, previous glucocorticoid therapy, underlying malignancy, operator inexperience, multiple lead placement, advanced patient age, oral anticoagulant use, 13 frequent generator replacement, heart failure, fever before device implantation, 14 use of temporary pacing catheters, 14 nonpectoral (abdominal or thoracoscopic) implantations, 15,16 and renal dysfunction.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…8,[25][26][27][28] CIED infection within 2 weeks of pocket manipulation is most commonly attributable to S aureus infection. 29,30 Streptococci, propionibacterium species, corynebacterium species, Gramnegative bacilli, nontuberculous mycobacteria, aspergillus, coxiella species, and candida can occasionally cause CIED infections.…”
Section: Microbiologymentioning
confidence: 99%